2011
DOI: 10.1016/j.bbamem.2011.06.019
|View full text |Cite
|
Sign up to set email alerts
|

The membrane-active regions of the dengue virus proteins C and E

Abstract: We have identified the membranotropic regions of proteins C and E of DENV virus by performing an exhaustive study of membrane rupture induced by two C and E-derived peptide libraries on model membranes having different phospholipid compositions as well as its ability to modulate the DEPE L(β)-L(α) and L(α)-H(II) phospholipid phase transitions. Protein C presents one hydrophobic leakage-prone region coincidental with a proposed membrane interacting domain, whereas protein E presents five membrane-rupture zones … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 61 publications
2
24
0
Order By: Relevance
“…The observed peptide-lipid membrane interactions are not merely charge based, as binding and disruption occurred with both zwitterionic POPC vesicles as well as negatively-charged 9∶1 POPC/POPG vesicles. Supporting these observations, a recent study of the membrane disruption ability of overlapping peptides from dengue virus type 2 C and E proteins showed that E protein stem derived peptides were highly disruptive to liposomes prepared with a wide variety of lipid compositions [19].…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…The observed peptide-lipid membrane interactions are not merely charge based, as binding and disruption occurred with both zwitterionic POPC vesicles as well as negatively-charged 9∶1 POPC/POPG vesicles. Supporting these observations, a recent study of the membrane disruption ability of overlapping peptides from dengue virus type 2 C and E proteins showed that E protein stem derived peptides were highly disruptive to liposomes prepared with a wide variety of lipid compositions [19].…”
Section: Resultsmentioning
confidence: 80%
“…The lack of apparent disruption of cellular plasma membranes and other viral membranes may be due to lipid composition, protein incorporation, or active repair of cellular membranes. Dengue virus particles bud from internal endoplasmic reticulum membranes of infected cells and so likely have a different composition from the plasma membrane, although the membrane disruption activity of stem region peptides is not strongly influenced by lipid membrane composition [19].…”
Section: Resultsmentioning
confidence: 99%
“…We have recently identified the membrane-active regions of a number of viral proteins by observing the effect of peptide libraries on model membrane integrity, including HCV NS4B [19][20][21][22][23]. These results allowed us to propose the location of different segments in these proteins that should be implicated in protein-lipid and protein-protein interactions.…”
Section: Introductionmentioning
confidence: 92%
“…Particular attention has also been devoted to the effect of additional membranotropic sequences on the overall fusogenicity. The presence of additional fusogenic sequences was evidenced in Sendai F1 [34], Measles F1 [35], SARS-CoV S2 [36], Hepatitic C virus E1 and E2 [37], Dengue E [38,39] and Herpes Virus gB and gH [40][41][42]. The idea that a single fusion peptide is the solely responsible for the complete membrane fusion event has been substituted by the assumption that a concerted action of different membranotropic regions is necessary for membrane interacting/perturbing activity.…”
Section: Membranotropic Peptides and Fusion Abilitymentioning
confidence: 99%